2018
DOI: 10.1002/cctc.201800142
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Oxazolidinones and Derivatives through Three‐Component Fixation of Carbon Dioxide

Abstract: An effective three‐component fixation of atmospheric CO2 with readily available 1,2‐dichloroethane and aromatic amine toward oxazolidinones catalyzed by in situ NHC was developed. The reaction occurred in good to excellent yields with good generality and wide functional group tolerance, including challenging steric hindered substituted‐dichloroethane (e.g. 1,2‐dichloropropane and 2,3‐dichlorobutane). The catalytic system is not sensitive to air and moisture, and high yield of oxazolidinone was achieved even wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 75 publications
(72 reference statements)
0
13
0
Order By: Relevance
“…Authors also demonstrated by means of control experiments that carbonate ions were not the C1 source of the reaction. Finally, oxazolidinones could be obtained in high yields from a three-component reaction among CO 2 , 1,2-dichloroethane and aromatic amines catalyzed by N-heterocyclic carbene obtained in situ from an ionic liquid (Scheme 24) [181]. However, the reaction with 2,3-dichlorobutane afforded the corresponding 4,5-dimethyl-3-aryloxazolidin-2-ones in very low yields (28-40%).…”
Section: Scheme 13mentioning
confidence: 99%
“…Authors also demonstrated by means of control experiments that carbonate ions were not the C1 source of the reaction. Finally, oxazolidinones could be obtained in high yields from a three-component reaction among CO 2 , 1,2-dichloroethane and aromatic amines catalyzed by N-heterocyclic carbene obtained in situ from an ionic liquid (Scheme 24) [181]. However, the reaction with 2,3-dichlorobutane afforded the corresponding 4,5-dimethyl-3-aryloxazolidin-2-ones in very low yields (28-40%).…”
Section: Scheme 13mentioning
confidence: 99%
“…It has been well known that the reactions of CO 2 with different amino compounds can produce various organic chemicals, such as urea, [13,14] bis‐substituted urea, [15] carbamates [16–18] (Scheme 1, Eq. 1–3) and oxazolidinones (i. e., cyclic urethanes), [19–25] revealing that the activation of CO 2 by alkaline amino‐compounds in cooperative combination of a suitable catalyst is of fundamental importance in CO 2 ‐involed synthesis protocols. As for the synthesis of oxazolidinones via CO 2 ‐fixation using high‐energy N‐containing compounds (such as ethanolamines, aziridines or ethylene epoxide) featured with strict structural limitation (Scheme 1, Eq.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of CO2 as a C1 building block for synthesizing high-value organic chemicals has gained much more attention. Converting CO2 to industrial chemical products is a route for recycling carbon and carbon-containing materials [8,9]. Cyclic carbamates are one of the most important target compounds of conversion of CO2, having several applications in both the chemical industry and organic chemistry [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%